Cloning and Clone Analysis of GRA1 Gene from Local Isolate Toxoplasma gondii Tachyzoite - Subekti, Didik T; Artama, W.T; Sulistyaningsih, E; Poerwanto, S.H; Sari, Y; Bagaskoro, F (Indonesian Animal Sciences Society, 2008)
The GRA1 gene of Toxoplasma gondii encoding protein called GRA1 protein. GRA1 protein known to be immunogenic and essentialy involved in modification of parasitophorus vacoule which has role in immune evasion and virulency of organism. The local isolate of T. gondii is successfuly isolated and known as highly pathogenic isolate similarly as its RH strain. Unfortunately, the homology sequence of GRA1 gene between those isolate still unknown. The purpose of the research are to clone the GRA1 gene and to analyze the homology from pathogenic T. gondii isolate and RH strain. Tachyzoite of T. gondii was grown in mice peritoneum by intraperitoneal injection. Then, total mRNA was isolated and purified. cDNA was synthesized from mRNA and then amplified using F1 dan R1 primers to get clone of GRA1 from local isolate. Homology analysis was perform using several bioinformatic softwares. The result showed that cDNA of GRA1 from local isolate has 84% homologs with RH strain of T.gondii. However, when subsequently editing performed to parts of suspected non coding sequence of cDNA GRA1 to get CDS of GRA1, the homology was increase to 100% compare to CDS of GRA1 of RH strain. Key words: GRA1, Toxoplasma gondii, Clonning, Expression